Sportwissenschaft - Fritz C; Hager A (Deutsche Zeitschrift für Sportmedizin)
Most patients with congenital heart diseases profit from physical activity and physical exercise training. Physical activity improves exercise capacity and, therefore, reduces the risk of suffering from cardiovascular and chronic diseases. Patients with former congenital heart diseases have reduced physical capacity compared to the healthy population despite having no hemodynamic sequelae. They should be encouraged to do physical activities to improve quality of life and to prevent acquired cardiovascular disease. Nevertheless, precautions have to be taken in some patients and recommendations have to be made according the individual residual findings in order to minimize risks of cardiac events.This article summarizes the recent sport recommendations for adults with congenital heart diseases in consideration of the diagnostic findings, medication and patients requests and expectations. As sport eligibility notably correlates with the recent findings, it is more useful to focus on hemodynamic function than on the type of defect.The majority of sport activities can be recommended for most patients. Fundamentally, annual medical surveillance needs to be conducted to reassess the sport recommendations considering recent diagnostic findings. Specific restrictions should only be addressed in case of medical issues. These restrictions should be discussed individually with the patient, taking any diagnostic findings and the patients requests as well as their expectations into account. KEY WORDS: Congenital Heart Disease, Recommendation, Restriction, Residual Findings